Brief Report: Exercise and Blood Pressure in Older Adults—An Updated Look. (29th October 2018) - Kelley, George A.; Kelley, Kristi S.
Abstract : Background/Objectives . Raised blood pressure is a major problem in older adults. Using a random-effects model, a recent meta-analysis reported statistically significant reductions in both resting systolic blood pressure (SBP) and diastolic blood pressure (DBP) as a result of aerobic, resistance, and combined aerobic and resistance exercise in adults ≥ 65 years. To provide more objective information regarding this nonpharmacologic approach, this study applied more robust methods to this data. Design . Meta-analysis of 41 randomized controlled trials representing 96 groups (52 exercise; 44 control). Setting . Any location where a randomized controlled trial could be conducted. Participants . Adults ≥ 65 years. Intervention . Trials ≥ 2 weeks that included aerobic, resistance, and/or combined aerobic and resistance exercise as the intervention. Measurements . The recently developed inverse heterogeneity model (IVhet) was used to pool findings and the Doi plot was used to examine for small-study effects. Absolute and relative differences between the IVhet and random-effects model were also calculated. Data were reported using the mean difference (exercise minus control) with nonoverlapping 95% confidence intervals considered statistically significant. Results . Statistically significant reductions in resting blood pressure were found as a result of aerobic exercise (SBP, -4.7 mmHg, 95% CI, -7.7 to -1.8; DBP, -2.0 mmHg, 95% CI -3.13 to -0.9), SBP but not DBP for resistance training (SBP, -7.0 mmHg, 95% CI, -10.5 to -3.4; DBP, -1.2 mmHg, 95% CI -2.7 to 0.3), and both SBP and DBP for combined aerobic and resistance training (SBP, -5.5 mmHg, 95% CI, -8.3 to -2.7; DBP, -3.7 mmHg, 95% CI -4.8 to -2.7). Conclusions . Exclusive of changes in DBP congruent with resistance training, exercise (aerobic, resistance, and combined aerobic and resistance) reduces resting SBP and DBP in older adults. These findings have practical implications when considering exercise for the prevention and treatment of raised blood pressure in older adults.